2012
DOI: 10.1007/s10853-012-6426-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of carbon fibres from a pyrolysed and graphitised liquid crystalline cellulose fibre precursor

Abstract: Regenerated cellulose fibres, spun from a liquid crystalline precursor, were pyrolysed at temperatures in the range 400-2,500°C. Raman spectroscopy and X-ray diffraction showed that the degree of graphitisation of the fibre increased with increasing temperature. Electron microscopy, however, suggested that the fibres have a skin-core structure. This observation was confirmed by micro-Raman analysis, whereupon the ratio of the intensities of the D and G bands shows that the skin consists of a graphitised struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
52
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 31 publications
13
52
0
2
Order By: Relevance
“…The increase in the I D /I G ratio is in agreement with the observations of electrospun cellulose-based carbon nanofibers [45], regenerated liquid crystalline cellulose-based carbon fibers [55], Japanese cedar wood [52], softwood [56], glassy carbons from polyfurfuryl alcohol [57] and carbon aerogels [58, but is opposite to that observed in PAN-based carbon fibers [59], where the I D /I G values were found to decrease with rising temperature. The rise in I D /I G ratios demonstrates that graphene-like structures grow by consuming and reorganizing more amorphous structures as they are exposed to high temperatures [60].…”
Section: Assessment Of Raman Spectrasupporting
confidence: 87%
See 1 more Smart Citation
“…The increase in the I D /I G ratio is in agreement with the observations of electrospun cellulose-based carbon nanofibers [45], regenerated liquid crystalline cellulose-based carbon fibers [55], Japanese cedar wood [52], softwood [56], glassy carbons from polyfurfuryl alcohol [57] and carbon aerogels [58, but is opposite to that observed in PAN-based carbon fibers [59], where the I D /I G values were found to decrease with rising temperature. The rise in I D /I G ratios demonstrates that graphene-like structures grow by consuming and reorganizing more amorphous structures as they are exposed to high temperatures [60].…”
Section: Assessment Of Raman Spectrasupporting
confidence: 87%
“…The values of the I D /I G ratio increased from 1.95 to 2.33 with rising temperature, which is typical of the onset of a carbonized structure [55]. The increase in I D /I G ratio, shown in Table 4, suggests that the apparent in-plane crystallite size (L a ) increases with rising temperature, which is in agreement with the findings of the X-ray diffraction measurements.…”
Section: Assessment Of Raman Spectrasupporting
confidence: 87%
“…The oxygen introduced in Tuinistra and Koenig eq 4. However, in the cases of liquid crystalline cellulose-based CFs [27] and aramid-based CFs [11], the variation in the I D /I G value was opposite to that observed in the PAN based carbon nanofibers. They explained that the I D / I G ratios increased because the crystallites consisting of cyclic structures containing 4 or 5 carbon atoms grew, and this contributed to the Raman scatter as the carbonization temperature was increased from 500 to 1100 o C. They also concluded that higher carbonization temperatures above 1100 o C are required to obtain a measurable in-plane crystallite size (L a ) from both the XRD and Raman spectroscopy methods.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Raman spectroscopy has been employed for a number of years to characterise both structure and mechanical properties of carbon fibres [10][11][12][13][14][15] and is now used extensively to characterise different forms of graphene-based materials [7,8,16,17].…”
Section: Introductionmentioning
confidence: 99%